2020
DOI: 10.1007/s00167-020-06332-7
|View full text |Cite
|
Sign up to set email alerts
|

Transtibial pullout repair of medial meniscus posterior root tears: effects on the meniscus healing score and ICRS grade among patients with mild osteoarthritis of the knee

Abstract: We would like to thank Editage (www.editage.jp) for English language editing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Of the eight level IV studies (Table 2) included in this systematic review, all studies focused on repair of MMPRTs. [6][7][8]21,24,[30][31][32] All studies showed improvement in clinical outcomes for repair of MMPRTs. Lee et al, Liu et al and Nha et al 6,24,32 reported that a significant improvement in both radiographic and clinical outcomes with patients undergone repair treatment.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Of the eight level IV studies (Table 2) included in this systematic review, all studies focused on repair of MMPRTs. [6][7][8]21,24,[30][31][32] All studies showed improvement in clinical outcomes for repair of MMPRTs. Lee et al, Liu et al and Nha et al 6,24,32 reported that a significant improvement in both radiographic and clinical outcomes with patients undergone repair treatment.…”
Section: Resultsmentioning
confidence: 97%
“…Three studies used second-look arthroscopy to evaluate surgical outcomes. 8,21,24 Seo et al 8 found that all patients showed clinical improvement despite findings of incomplete or failed healing on second-look arthroscopy after repairing. However, Lee et al 30 reported that the healing status of the repaired meniscus may relate to clinical outcomes, the stable healed meniscus showed better clinical outcomes and have less complaint compared with unhealed meniscus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations